Soap operas won’t wash for wildlife - Somerville, K; Dickman, A; Johnson, P; Hart, A (Wiley Open Access, 2021)
1. Natural history documentaries are a globally important source of information about wildlife, conservation and environmental issues and they are the closest many will get to seeing featured animals and their behaviour in the wild. They are entertainment, certainly, but may also inform people’s knowledge of the natural world and influence their ideas on conservation of species and habitats. We locate our perspective in the existing literature analysing wildlife documentary making and its effects. 2. We argue that a conspicuous preoccupation with the ‘personalisation’ of individual animals and the injection of false jeopardy in recent wildlife documentaries leads to significant misinformation and creates problems for public understanding of wider conservation. 3. We illustrate our point by detailing episodes from the BBC natural history series Dynasties, discussing personalisation, anthropomorphism and the use of jeopardy to gain emotive impact and audience engagement. We find that narratives are framed around a single individual, that “stories” are framed as soap-operas, that jeopardy is emphasised throughout and that animals are endowed with the capacity to be aware of, and work towards, the dynasties of the title. 4. With conservation increasingly relying on public support, we argue that it is important that people are presented with factually correct information, and portraying wild animals as soap-opera style characters is neither honest nor helpful.